Biodegradable polymers suitable for tissue engineering and drug delivery systems - Kujundziski Aleksandra Porjazoska; Dragica Chamovska (Zaštita Materijala)
Biodegradable polymers for medical and pharmaceutical application have been in the focus of scientific interest in the last two decades. Among the others, features like biocompatibility, supportive cell proliferation and biodegradation are considered as crucial in the fabrication of scaffolds in tissue engineering and controlled drug delivery systems. Polymers based on polyesters, polyethers, polyanhydrides, poly(ether esters), poly(ortho esters), poly(amino acids) are very significant for the application in medicine and pharmaceutics. Porous polymer matrices in tissue engineering encourage the growth of cells, at the same time allowing the exchange of nutrients and residuals. Drug delivery systems, where biological agent is dispersed / dissolved in the polymer matrix, act as reservoirs, while drug carriers are those systems where the active substance and matrix are chemically bonded. Of particular interest to many researchers are the systems in which degradation profile of polymer matrix is crucial in the determination of the rate by which the medicament is released. Biodegradable nanosized systems as devices of controlled release or selected targeting of active component attract significant attention. This paper provides a brief outline of biodegradable polymers, the properties important for their application in medicine, with particular interest in their hydrolytic degradation, and at the same time, it will serve as a basis for further research in this area.